Investigating the effect of internet addiction on the tendency to marital infidelity in couples in Shiraz - Baboo, Nasrin (2021)
Background and Purpose: The purpose of this study was to investigate the effect of Internet addiction on the tendency to marital infidelity in couples in Shiraz. Method: The statistical population includes all men and women who referred to counseling centers in Shiraz for marriage counseling in 2015. These people completed the Internet Addiction Questionnaire and were divided into two groups: Internet addicts and normal. Samples were selected by available sampling method from Shiraz city counseling centers, 60 Internet addicts and 60 normal people. Findings(Results): The results showed that there is a significant difference between Internet addicts and people who use the Internet normally in the tendency to betray and addicted people have a greater tendency to betray. The difference between men and women in the tendency to betray is not significant and the duration Marriage is also a poor predictor of marital infidelity. Conclusion: The results of this study showed that people with Internet addiction are more prone to betrayal. This issue can be both a sign of betrayal and a cause for it. In any case, the extreme presence in cyberspace facilitates the tendency to betrayal in people.